Medical outcomes study social support survey (MOS-SSS) in patients with chronic disease: A psychometric assessment - Merino-Soto, Cesar; Núñez Benítez, Miguel Ángel; Domínguez-Guedea, Miriam Teresa; Toledano-Toledano, Filiberto; Moral de la Rubia, José; Astudillo-García, Claudia I.; Rivera-Rivera, Leonor; Leyva-López, Ahidée; Angulo-Ramos, Marisol; Flores Laguna, Omar Arodi; Hernández-Salinas, Gregorio; Rodríguez Castro, Jorge Homero; et al. (Frontiers in Psychiatry, 2023)
Purpose: Currently, information on the psychometric properties of the Medical Outcomes Study Social Support Survey (MOS-SSS) for patients with chronic disease in primary health care, suggests problems in the dimensionality, specifically predominant unidimensionality in a multidimensional measure. The aim of this study was to determine the internal structure (dimensionality, measurement invariance and reliability) and association with other variables. Methods: A total of 470 patients with chronic disease from a Family Medicine Unit at the Instituto Mexicano del Seguro Social, IMSS, with a mean age of 51.51 years were included. Participants responded to the Questionnaire of Sociodemographic Variables (Q-SV), SF-36 Health-Related Quality of Life Scale–version 1.1, and MOS-SSS. Results: Nonparametric (Mokken scaling analysis) and parametric (confirmatory factor analysis) analyses indicated unidimensionality, and three-factor model was not representative. A new 8-item version (MOS-S) was developed, where measurement invariance, equivalence with the long version, reliability, and relationship with the SF-36 were satisfactory. Conclusion: The MOS-SSS scale is unidimensional, and the shortened version yields valid and reliable scores for measuring social support in patients with chronic disease at the primary health care.